PENGARUH RETURN ON ASSETS (ROA) DAN EARNING PER SHARE (EPS) TERHADAP HARGA SAHAM PADA PERUSAHAAN SEKTOR PERBANKAN (BUMN) YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2016-2023 - Safitri, Zaini; Hulu, Paolinus; Johan, Muhammad (Jurnal Bisnis Manajemen dan Akuntansi, 2024)
ABSTRAC Credit growth disbursed by the banking industry in 2023 slowed down compared to 2022. In 2023, banking loans will grow by around 10.38% on an annual basis (YoY). The achievement of banking credit disbursement in 2023 was recorded to grow slower than in 2022 which was able to reach 11.35% YoY. Perry Warjiyo (2024) stated that "Credit growth is more supported by investment credit and working capital, at 12.26% and 10.05%, respectively". (https://m.kontan.co.id) Therefore, this study aims to examine the effect of Return On Assets and Earning per Share on Stock Prices with the object of the study, namely Banking Companies Listed on the Indonesia Stock Exchange for the 2016-2023 Period. The design of this study uses an associative research design, which is a study that asks about the relationship between two or more variables. The dependent variable used is the Stock Price, and the Independent variable used is ROA (X1) and EPS (X2). The sampling technique used in this study is purposive sampling, so that a sample of 4 companies was obtained. The data used is secondary data, namely in the form of the company's financial statements. The results of the study using a multiple linear regression analysis test obtained the regression formula Y=1441,546+289,001X1+8,069X2 which means that if there is no increase or increase in ROA and EPS, the Stock Price is Rp1,441,546, and if there is an increase in ROA by one, the Stock Price has increased by Rp289,001, and also if there is an increase in EPS by one, the Stock Price has increased by Rp8, 069. This shows that ROA and EPS simultaneously have a positive effect on the Stock Price. In the Determination Coefficient test simultaneously, a result of 0.484 was obtained, which means that ROA (X1) and EPS (X2) simultaneously have an influence of 48.4% on the Stock Price and the remaining 51.6% is influenced by other variables. In the t test ROA (X1), Tcount result was obtained of 2,004 > Ttable of 1,697, this shows that ROA (X1) partially has a significant effect on the Stock Price (Y) and the result of the t-test EPS (X2) obtained Tcount result of 5,194 > TTable of 1,697, this shows that EPS (X2) partially has a significant effect on the Stock Price (Y). In the f test, the results of Fcount of 13.626 > the ftable of 3.32 things show that ROA (X1) and EPS (X2) simultaneously have a positive influence on the Stock Price (Y). Keywords: Return On Assets (ROA), Earning Per Share (EPS), Stock Price.